Emerging Targeted Delivery Strategies of Nanosystems for Ischemic Stroke Treatment - Ren JX; Ma HY; Yin WJ; Li YK; Lei SY; Liu JC; Yang Y; Guo ZN (International Journal of Nanomedicine)
Jia-Xin Ren,1,* Hong-Yin Ma,1,* Wen-Jing Yin,1 Yi-Kai Li,2 Shuang-Yin Lei,1 Jia-Cheng Liu,1 Yi Yang,1 Zhen-Ni Guo1,3 1Stroke Center, Department of Neurology, the First Hospital of Jilin University, Chang Chun, People’s Republic of China; 2The First Norman Bethune Clinical Medical College, Jilin University, Chang Chun, People’s Republic of China; 3Neuroscience Research Center, Department of Neurology, the First Hospital of Jilin University, Chang Chun, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Yang, Department of Neurology, the First Hospital of Jilin University, Xinmin Street 1#, Changchun, 130021, People’s Republic of China, Tel +86-13756661217, Fax +86-431-88782378, Email yang_yi@jlu.edu.cn Zhen-Ni Guo, Department of Neurology, the First Hospital of Jilin University, Xinmin Street 1#, Changchun, 130021, People’s Republic of China, Tel +86-18186872986, Fax +86-431-88782378, Email zhen1ni2@jlu.edu.cnAbstract: Ischemic stroke is a leading cause of death and severe disability worldwide. Current treatments mainly focus on reperfusion and neuroprotection. However, due to limitations like a narrow treatment window, single therapeutic targets, and side effects, drug therapy effectiveness is often unsatisfactory. Additionally, the blood-brain barrier (BBB) and the pathophysiological changes following ischemia pose challenges in stroke treatment. Recent developments in nanomaterials have enabled the design of multifunctional drug delivery nanosystems to advance stroke therapeutic approaches. These novel treatments significantly overcome the shortcomings of current therapies and improve efficacy. This review comprehensively summarizes innovative strategies for drug delivery nanosystems, which include crossing the BBB to target the ischemic region and controllable release in a responsive manner. Smart nanosystems, due to the modification of specific ligands and/or cell membranes, can cross the BBB to target the ischemic region for precise treatment, achieving controlled release and specific accumulation of drugs through intelligent molecular switching. Combining different strategies to build drug delivery nanosystems allows for positioning and targeted accumulation of drugs in the ischemic region, thereby extending the therapeutic time window and synergistically improving the neuroprotective effects. Such combinations provide a powerful strategy for developing novel ischemic stroke treatments and establishing targeting delivery nanosystems. Furthermore, the review summarizes the challenges encountered by multifunctional drug delivery nanosystems including clinical translation, drug loading capacity, and safety concerns, and potential solutions. Keywords: ischemic stroke, nanosystems, targeting therapy, blood-brain barrier, controllable release